The Australian Study of HIV and Injecting Drug Use. Part 11: Predicting exposure to hepatitis C and hepatitis B - Carruthers, Susan; Phillips, M.; Loxley, Wendy; Bevan, J. (Taylor and Francis, 1997)
Researchers agree that while hepatitis B maybe in control, hepatitis C is present in epidemic proportions among injecting drug users and that current HIV prevention strategies have not been sufficient to halt the spread of this hepatitis virus, although there is some evidence to suggest that incidence rates are stabilizing. Since there is no effective cure and it is unlikely that a vaccine will become available in the foreseeable future all efforts to control the spread of hepatitis C must rely on education and prevention strategies. The Australian Study of HIV and Injecting Drug Use is a cross-sectional national study designed to investigate exposure to and risks for infection with blood-borne viruses. Of those volunteering a usable blood sample for hepatitis C antibody and hepatitis B core antibody testing 55% and 19%, respectively, returned reactive test results. Logistic regression statistical models were used to identify risk factors for hepatitis C and hepatitis B. Risk factors for hepatitis C were identified as duration of use, use of opiates on last injecting occasion, education level, treatment status and having a history of sexually transmissible diseases. Risk factors associated with hepatitis B were duration of use, and use of opiates on last injecting occasion. The lack of identifiable risk factors for hepatitis B suggest that past rather than current injecting and sexual behaviour parterns are required to predict accurately risk of exposure to hepatitis B. In addition to this, one-third of respondents reported being vaccinated against hepatitis B. Respondents perceived themselves to be at greater risk from hepatitis C than from hepatitis B or HIV. A discussion of strategies needed to prevent the spread of the hepatitis viruses will be presented along with recommendations for further research.